Evaluation of antibiotic use in pneumonia patients at bahteramas hospital using the gyssens method - Agustiana, Agustiana; L, Adryan Fristiohady.; Arba, Muhammad; Jabbar, Asriullah; Suryani, Suryani; Akib, Nur Illiyyin (Science Midwifery, 2025)
Pneumonia is one of the leading causes of morbidity and mortality due to lower respiratory tract infections, with treatment heavily reliant on antibiotic administration. However, irrational use of antibiotics significantly contributes to the rise of antimicrobial resistance. This study aimed to evaluate the rationality of antibiotic use in adult pneumonia patients at RSUD Bahteramas, Southeast Sulawesi Province, using the Gyssens method. A total of 100 hospitalized patients who met the inclusion criteria from January to December 2024 were included. Data were analyzed using the Gyssens method to assess the appropriateness of antibiotic therapy based on indication, dosage, duration, route, and timing of administration. The results showed that only 41% of antibiotic use was classified as rational (category 0), while 59% was deemed irrational (categories I–V). Levofloxacin was the most frequently used antibiotic (63%), although its use often did not align with clinical guidelines. Most patients required antibiotics for 3–4 days, consistent with recommendations for mild to moderate pneumonia. Nonetheless, inappropriate use was still observed, particularly in prolonged therapy durations and antibiotic combinations without clear indications. These findings underscore the importance of strengthening adherence to clinical guidelines and conducting regular evaluations to prevent resistance and improve treatment outcomes.